Psychological aspects of the professional values system generating in pre-set aviation personnel - Денисюк, Л.М. (Proceedings of National Aviation University (archive), 2010)
The article pays attention on that fact the professional activity is stipulated by the values system. The paper looks at major problems related to the professional values system of the students generating. The author proposes some approaches to initiation of the conscious gaining of the professional values for their functioning on the actual performance level.